Respostas
respondido por:
1
5+4(x-1)=18x-9/3
3.[5+4(x-1)]= 18x-9
3[5+4x-4] = 18x-9
3[4x+1] = 18x - 9
12x + 3 = 18x -9
3+9 = 18x - 12x
12 = 6x
x = 12/6
x = 2
3.[5+4(x-1)]= 18x-9
3[5+4x-4] = 18x-9
3[4x+1] = 18x - 9
12x + 3 = 18x -9
3+9 = 18x - 12x
12 = 6x
x = 12/6
x = 2
respondido por:
0
5+4(x-1)=
15 + 12(x-1) = 18x - 9
15 + 12x - 12 = 18x - 9
18x - 12x = 15 -12+9
6x = 12
x = 2
15 + 12(x-1) = 18x - 9
15 + 12x - 12 = 18x - 9
18x - 12x = 15 -12+9
6x = 12
x = 2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás